Surgical management of traumatic atlantoaxial subluxation in two cats. Issue 2 (July 2021) - Gilbert, Emma; Driver, Colin J
Case series summary: We describe here the surgical management of two pure breed cats with traumatic atlantoaxial subluxation. One cat was ambulatory tetraparetic on presentation and the second was tetraplegic, both with cervical spinal pain and acute onset of paresis with subsequent deterioration. MRI was performed in both cases, demonstrating spinal cord injury. Flexed lateral cervical radiographs were needed to confirm atlantoaxial subluxation in one case. CT was performed for surgical planning and surgical stabilisation was achieved with threaded pins and polymethyl methacrylate (PMMA) cement; odontoidectomy was required in one case. Both cats showed improvement postoperatively, with no complications or deterioration seen. Following surgery, one cat made a complete recovery; however, the second cat retained significant deficits. Relevance and novel information: We present the first report of surgically managed atlantoaxial subluxation of traumatic aetiology in cats, and report its occurrence in two novel breeds for this disease, Ragdoll and Persian. One case required odontoidectomy due to previous fracture and malunion of the odontoid process of the axis; both cases underwent surgical stabilisation of the atlantoaxial joint utilising multiple threaded pins and PMMA cement without transarticular implants – a technique that has not been previously reported in cats.